The role of social media on the voting behavior of middle-aged and above educators of Bahawalpur during the general elections of 2018 - Sadiq, Rabia (Journal of Political Studies, 2025)
Social media sites were greatly used by political parties and the masses in the general elections of 2018 in Pakistan. The influence of social media on the voting behavior of youth has been researched extensively. The objective of this study is to observe how social media has influenced the voting behavior and political participation of middle-aged and elder educators of Bahawalpur. Qualitative research has been conducted with the help of a structured questionnaire, and descriptive analysis is used for analysis. The sample size is 25 based on convenience sampling. The findings reveal that Facebook and YouTube are the most used platforms by middle-aged educators. The results of this research show that the voting behavior of the middle-aged educators of Bahawalpur has been influenced by the usage of social media sites.